Acquisitive Crime and Inflation in the United States: 1960–2012 - Rosenfeld, Richard (Journal of quantitative criminology, 2016)
Objectives Inflation is conspicuous by its absence from recent research on crime and the economy. We argue that price inflation increases the rate of crimes committed for monetary gain by fueling demand for cheap stolen goods. Methods The study includes inflation along with indicators of unemployment, GDP, income, consumer sentiment, and controls in error correction models of acquisitive crime covering the period from 1960 to 2012. Both short- and long-run effects of the predictors are estimated. Results Among the economic indicators, only inflation has consistent and robust short- and long-run effects on year-over-year change in the offense types under consideration. Low inflation helps to explain why acquisitive crime did not increase during the 2008–2009 recession. Imprisonment rates also have robust long-run effects on change in acquisitive crime rates. Conclusions Incorporating inflation into studies of crime and the economy can help to reduce the theoretical and empirical uncertainty that has long characterized this important research area in criminology.